Environmental testing standard in Malaysian automotive industry: a case study of the vehicle component electrical door control module / Nurul Hayati Abdul Wahid. - Abdul Wahid, Nurul Hayati (2013)
Environmental crisis is a global issue that generates a massive impact and consciousness in various sectors including in the automotive industry. Environmental sustainability is the ability to sustain devices or qualities that are valued in the physical environment. In the automotive environmental factors, each of vehicle components performance and reliability has to be ensured comply with the requirement under the critical environment characteristics. The purpose of this research paper is to identify the environmental experiment methods of the automotive components in order to establish environmental testing standards and guidelines. This study furthermore examine the characteristics and performance of the vehicles component based on the established environmental experiment guidelines, and then analyze the data of the experiment of the Electrical Door Control Module (EDCM) components, in order to validate the environmental experiment criteria, conform to the automotive environmental regulation and requirements. This research paper of the automotive component (EDCM) environmental sustainability assessment, involved details study of the experimental procedures, which is determine according to the company requirement of the component reliability test specification, and based on automotive environmental standards references of the Japanese Automobile Standard, General Rules of the Environmental Testing Methods for Automotive Electronic Equipment (JASO, 1994); and Japanese Industrial Standard (JIS, 1999 and 1994). This research describes a structured standard of the testing method related to the environmental factors for automotive component development. Based on the formulate criterion in this environmental testing standards, this paper explain the environmental characteristics framework which can be measure and becomes an effective tools to support and evaluate environmental criteria items in vehicle component product testing and development process. Keywords: Environmental Testing Standard, Environmental Sustainability, Automotive environment characteristics, Automotive Component, Electrical Door Control Module, Automotive component experimental methods.